Analytical model of asymmetrical Mixed-Mode Bending test of adhesively bonded GFRP joint - M. Ševčík; P. Hutař; A. P. Vassilopoulos; M. Shahverdi (Fracture and Structural Integrity)
This paper presents new analytical model of asymmetric mixed-mode bending (MMB) specimen of adhesively bonded pultruded GFRP joints. An easily applicable relationship for the calculation of the strain energy release rate of the asymmetric MMB specimens is proposed based on the beam theory. The model is capable to analyze stacking sequence as well as various crack propagation paths. In the paper the effect of the various fiber bridging length and different crack propagation paths is analyzed analytically and supported by experimental results. The methodology and results presented in this paper could be utilized for the design of both joint geometry and lay-up of the laminates constituting the joint or for the prediction of the fracture behavior of such structures.